Pengembangan LMS Dengan Model Project Based Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas X RPL SMK Negeri 2 Mojokerto - Firda Nur Laily; Ekohariadi Ekohariadi (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
Web Programming learning in Vocational High Schools still faces various challenges, such as teacher-dominated approaches, lack of student participation, and the absence of a Learning Management System (LMS) that can effectively support project-based learning methods. This study aims to develop an LMS system with a Project Based Learning (PjBL) model to improve the learning outcomes of class X Software Engineering students at SMK Negeri 2 Mojokerto. The research method used is Research and Development (R&D) with the ADDIE model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects studied were 35 students from class X RPL 1. Data were collected through validation from media experts, material validation, as well as pretest-posttest and project assessment. Data analysis was carried out by calculating the validity percentage, N-Gain, and using the Wilcoxon Signed Rank Test. The research findings indicate that the LMS that has been developed meets the eligibility standards as a learning tool and can improve student learning outcomes in cognitive and psychomotor aspects. LMS integrated with PjBL provides a more structured, interactive, and practice-based learning experience. Therefore, the resulting LMS can be an alternative choice in supporting Web Programming learning in vocational schools.